2002
DOI: 10.4319/lo.2002.47.6.1684
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of spring bacterial production in the North Atlantic Ocean

Abstract: Dissolved organic carbon (DOC), a major reservoir in the ocean carbon cycle, is produced by a profusion of plankton sources and processes but is consumed mainly by bacterioplankton. Thus bacterial metabolism regulates the entry of DOC into the longer scale global carbon cycle. Bacterial production (BP) is the routinely measured quantity for evaluating the roles of bacteria in carbon cycling. However BP cannot be measured directly and instead is estimated from related metabolic processes requiring the use of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 42 publications
7
37
0
Order By: Relevance
“…Furthermore, it has been recognized that prokaryotes, notably bacteria, play a key role in the decomposition of nonliving organic particles in the surface layers (Ducklow and Carlson 1992) and in mesopelagic waters (Cho and Azam 1988;Karl et al 1988). The latter two studies presented evidence that POC concentrations decrease with depth more rapidly than one would deduce from bacterial activity measurements.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, it has been recognized that prokaryotes, notably bacteria, play a key role in the decomposition of nonliving organic particles in the surface layers (Ducklow and Carlson 1992) and in mesopelagic waters (Cho and Azam 1988;Karl et al 1988). The latter two studies presented evidence that POC concentrations decrease with depth more rapidly than one would deduce from bacterial activity measurements.…”
mentioning
confidence: 71%
“…Bacterial carbon demand and remineralization rates are often deduced from bacterial production measurements, calculating respiration from an average bacterial growth yield of 20-30% (Nagata et al 2000;Ducklow et al 2002). Thus, the major fraction of the carbon flow mediated by heterotrophic bacteria, i.e., respiration, is deduced from measurements of a minor fraction, i.e., organic carbon production.…”
mentioning
confidence: 99%
“…Estimates of BP were typically reported in carbon units and converted to a standard rate of gC L Ϫ1 h Ϫ1 . Rates of leucine and thymidine incorporation were converted to carbon units using 3.1 kg C mol Leu Ϫ1 (SIMON and AZAM, 1989) and 1.89 kg C mol TdR Ϫ1 (DUCKLOW, KIRCHMAN, and ANDERSON, 2002), respectively. Bacterial production reported as change in cell abundance was converted to carbon units using 20 fg C cell Ϫ1 (LEE and FUHRMAN, 1987).…”
Section: Data Collection: Published Literaturementioning
confidence: 99%
“…The change was precipitated by new assessments of bacterial growth efficiency (BGE), which had been assumed to be ∼50%, 3-fold higher than the value of 15% suggested by new data (del Giorgio & Cole 1998, Carlson et al 1999. When the lower estimates of BGE were taken into consideration, it appeared that BP should be lower relative to PP, and that the BP:PP ratio cannot be higher than 0.15 (Ducklow et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The initial data indicated that heterotrophic BP was 30% of PP (BP:PP = 0.3) , Li et al 1993, Lochte et al 1993, consistent with other information available at that time from a range of freshwater and coastal marine systems (Cole et al 1988) as well as modeling studies (Williams 1981). However, the emergence of new data and knowledge necessitated a reformulation of these initial conclusions (Ducklow et al 2002). The change was precipitated by new assessments of bacterial growth efficiency (BGE), which had been assumed to be ∼50%, 3-fold higher than the value of 15% suggested by new data (del Giorgio & Cole 1998, Carlson et al 1999.…”
Section: Introductionmentioning
confidence: 99%